Pengaruh Moderasi Tata Kelola dalam Hubungan Inovasi dengan Kinerja UMKM: Studi Empiris pada Usaha Batik Jambi - Simarmata, Jonner; Almaududi, Said; Suryani, Arna (Universitas Batanghari Jambi, 2025)
This study aims to determine the moderating effect of governance on the relationship between innovation and the performance of MSMEs in the Jambi Batik business. Data collection techniques through the distribution of questionnaires to 103 respondents consisting of Jambi batik business actors, then analyzed through 2 (two) stages, namely simple regression and MRA (moderated regression analysis). The results of this study conclude that there is an influence of innovation and governance variables on MSME performance. However, the governance variable has not been able to moderate the influence of innovation variables on the performance of Jambi Batik MSMEs. This is due to the still low awareness of business owners towards governance so that it has not run well.